Back Cover Image, Volume 32, Issue 11. (6th November 2021) - Tohoku, Shota; Bordignon, Stefano; Chen, Shaojie; Zanchi, Simone; Bianchini, Lorenzo; Trolese, Luca; Operhalski, Felix; Urbanek, Lukas; Chun, K. R. Julian; Schmidt, Boris
Abstract : The Back cover image is based on the Original Article Single sweep pulmonary vein isolation on using the new third‐generation on laser balloon‐Evolution on in ablation on style using endoscopic ablation on system by Shota Tohoku et al., https://doi.org/10.1111/jce.15245 .